The thirty-nine steps Collins classics - Buchan, John (London : Harper Collins Publishers, 2012)
This classic spy thriller follows Richard Hannay, an ordinary man caught in an extraordinary web of espionage. When a neighbour reveals a deadly political conspiracy and is soon murdered, Hannay finds himself accused of the crime. Fleeing to the Scottish countryside, he must outwit both the police and enemy agents while racing to stop a plot that could plunge Britain into war. First published in 1915, the novel is celebrated for its fast-paced adventure, suspense, and the birth of the modern spy genre.
Keywords: English - Fiction Book